UbcH10 a Major Actor in Cancerogenesis and a Potential Tool for Diagnosis and Therapy - Presta, Ivan (Int J Mol Sci, 2020)
Malignant transformation is a multistep process in which several molecular entities become dysregulated and result in dysfunction in the regulation of cell proliferation. In past years, scientists have gradually dissected the pathways involved in the regulation of the cell cycle. The mitotic ubiquitin-conjugating enzymes UbcH10, has been extensively studied since its cloning and characterization and it has been identified as a constantly overexpressed factor in many types of cancer. In this paper, we have reviewed the literature about UbcH10 in human cancer, pointing out the association between its overexpression and exacerbation of cancer phenotype. Moreover, many recalled studied demonstrated how immunohistochemistry or RT-PCR analysis can distinguish normal tissues and benign lesions from malignant neoplasms. In other experimental studies, many of the consequences of UbcH10 overexpression, such as increased proliferation, metastasizing, cancer progression and resistance to anticancer drugs are reversed through gene silencing techniques. In recent years, many authors have defined UbcH10 evaluation in cancer patients as a useful tool for diagnosis and therapy. This opinion is shared by the authors who advertise how it would be useful to start using in clinical practice the notions acquired about this important moleculein the carcinogenesis of many human malignancies.